2011
DOI: 10.1111/j.1365-2885.2011.01280.x
|View full text |Cite
|
Sign up to set email alerts
|

Safety evaluation and treatment affect of LY2190416, a CB-1 antagonist/inverse agonist in growing beagle dogs

Abstract: The objective of this study was to assess the safe use of LY2190416, a cannabinoid receptor 1 receptor antagonist/inverse agonist, for obesity management in dogs. Twenty-four clinically normal young beagle dogs were administered LY2190416 at doses of 3, 9, or 18 mg/kg or placebo, orally, once daily for 13 weeks. Food consumption and body weight were determined, and dogs were evaluated for changes in hematology, clinical chemistry, urinalysis, and serum cortisol. LY2190416 had no significant effect on hematolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…Their body weight increased by 0.18±0.07 kg/week in male dogs and by 0.14±0.06 kg/week in female dogs. Nunamaker et al [ 19 ] reported that the body weight increased by 19.7 g/day in a control group of dogs. The relative organ weights were similar to those reported for a control group in a previous report [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Their body weight increased by 0.18±0.07 kg/week in male dogs and by 0.14±0.06 kg/week in female dogs. Nunamaker et al [ 19 ] reported that the body weight increased by 19.7 g/day in a control group of dogs. The relative organ weights were similar to those reported for a control group in a previous report [ 20 ].…”
Section: Discussionmentioning
confidence: 99%